Do prior studies matter?: Predicting proficiencies required to excel academically in law school at Makerere University, Uganda - Nalukenge, Betty; Wamala, Robert; Ocaya, Bruno (Quality Assurance in Education, 2016)
Introduction of law school admission examinations has increased the debate regarding the relevance of prior studies for the enrollees in the program. The key issues of contention are whether prior studies reliably predict academic achievement of enrollees, and demonstrate proficiencies required for admission in the program. The purpose of this paper is to use administrative records of law students at Makerere University – over a four-year stipulated period of bachelor’s studies – to investigate the above-mentioned issues further. Design/methodology/approach – Panel data of 2,485 records enable us to explore time variant and invariant factors in the course of bachelor’s candidature. Findings – About 81 per cent of differentials in academic achievement was found to be due to variation across students. In addition to confirming prior academic attainment as a contributing factor to variations in academic achievement, our findings affirm that competence in literature, history and divinity predicts success on the program. Research limitations/implications – Competence in these subjects (literature, history and divinity) certainly demonstrates proficiencies required by a student of law. Thus, admission based on competence in these subjects provides insights into proficiencies required by enrollees to excel academically in the program. Originality/value – Unlike prior studies, this study explores time-variant factors in the course of bachelor’s candidature, and is based on subjects taken during prior studies (secondary education) rather than a pooled index or weighted score adopted on admission to the program.
Keywords: Education; Performance; Higher education